Impact of Summer Air Temperature on Water and Solute Transport on a Permafrost‐Affected Slope in West Greenland - Sebastian F. Zastruzny; Ylva Sjöberg; Karsten H. Jensen; Yijing Liu; Bo Elberling (Water Resources Research)
Abstract In Arctic landscapes, the active layer forms a near‐surface aquifer on top of the permafrost where water and nutrients are available for plants or subject to downslope transport. Warmer summer air temperatures can increase the thickness of the active layer and alter the partitioning of water into evapotranspiration and discharge by increasing the potential evapotranspiration, the depth to the water table, and changing the flow paths but the interacting processes are poorly understood. In this study, a numerical model for surface‐ and subsurface cryo‐hydrology is calibrated based on field observations from a discontinue permafrost area in West Greenland considered sensitive to future climate changes. The validated model is used to simulate the effect of three summers with contrasting temperature regimes to quantify the variations in the active layer thickness, the resulting changes in the water balance, and the implications on solute transport. We find that an increase of summer air temperature by1.6°C, under similar precipitation can increase the active layer thickness by 0.25 m, increase evapotranspiration by 5%, and reduce the total discharge compared to a colder summer by 9%. Differences in soil moisture and evapotranspiration between upslope and downslope were amplified in a warm summer. These hydrological differences impact solute transport which is 1.6 times faster in a cold summer. Surprisingly, we note that future warmer summer with increase in permafrost thaw may not necessary lead to an increase in discharge along a hill slope with underlying permafrost.